Identification of the Myogenetic Oligodeoxynucleotides (myoDNs) That Promote Differentiation of Skeletal Muscle Myoblasts by Targeting Nucleolin - Shinji, Sayaka; Umezawa, Koji; Nihashi, Yuma; Nakamura, Shunichi; Shimosato, Takeshi; Takaya, Tomohide (Frontiers in Cell and Developmental Biology, 2021)
Herein we report that the 18-base telomeric oligodeoxynucleotides (ODNs) designed from the Lactobacillus rhamnosus GG genome promote differentiation of skeletal muscle myoblasts which are myogenic precursor cells. We termed these myogenetic ODNs (myoDNs). The activity of one of the myoDNs, iSN04, was independent of Toll-like receptors, but dependent on its conformational state. Molecular simulation and iSN04 mutants revealed stacking of the 13-15th guanines as a core structure for iSN04. The alkaloid berberine bound to the guanine stack and enhanced iSN04 activity, probably by stabilizing and optimizing iSN04 conformation. We further identified nucleolin as an iSN04-binding protein. Results showed that iSN04 antagonizes nucleolin, increases the levels of p53 protein translationally suppressed by nucleolin, and eventually induces myotube formation by modulating the expression of genes involved in myogenic differentiation and cell cycle arrest. This study shows that bacterial-derived myoDNs serve as aptamers and are potential nucleic acid drugs directly targeting myoblasts.